Securitizing Science: A Careful Consideration of Tradeoffs is Needed - Shih, Tommy (International Higher Education, 2025)
<h3 id="amid-growing-geopolitical-tensions-and-the-shift-toward-a-multipolar-world-research-security-has-emerged-as-a-critical-concern-for-academic-institutions-and-national-governments-while-efforts-to-protect-science-from-foreign-interference-and-intellectual-property-theft-are-increasing-many-current-measures-lack-empirical-grounding-clear-objectives-or-proven-effectiveness-this-paper-discusses-the-complex-tradeoffs-between-national-security-and-scientific-openness-highlighting-challenges-such-as-governance-conflicts-ethical-risks-and-politicization-of-research-oversight" data-pm-slice="1 1 []">Amid growing geopolitical tensions and the shift toward a multipolar world, research security has emerged as a critical concern for academic institutions and national governments. While efforts to protect science from foreign interference and intellectual property theft are increasing, many current measures lack empirical grounding, clear objectives, or proven effectiveness. This paper discusses the complex tradeoffs between national security and scientific openness, highlighting challenges such as governance conflicts, ethical risks, and politicization of research oversight.